2015
DOI: 10.1007/s10140-015-1295-8
|View full text |Cite
|
Sign up to set email alerts
|

Reformatted images of the thoracic and lumbar spine following CT of chest, abdomen, and pelvis in the setting of blunt trauma: are they necessary?

Abstract: Injuries involving the thoracic and lumbar (TL) spine in the setting of blunt trauma are not uncommon. At our institution, CT of the chest, abdomen, and pelvis (CT CAP) with dedicated reformatted images of the thoracolumbar spine (CT TL) is part of the standard work-up of patients following significant blunt trauma. The purpose of this study was to compare the detection rate of TL spine fractures on routine trauma CT CAP with reformatted CT TL spine images and determine whether these reformatted images detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…There is an increasing tendency of generating multiplanar reconstructed spinal images from CTAP examinations, particularly in the trauma setting. 4 This is primarily because they are more sensitive in detecting fractures compared with plain radiographs and avoid subjecting patients to a second CT spine study. 4 Similarly, in a nontrauma setting, especially oncology patients and patients with pyrexia of unknown origin, spinal reconstructions are routinely performed to assist in the detection of bone, paravertebral, and disc pathologies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is an increasing tendency of generating multiplanar reconstructed spinal images from CTAP examinations, particularly in the trauma setting. 4 This is primarily because they are more sensitive in detecting fractures compared with plain radiographs and avoid subjecting patients to a second CT spine study. 4 Similarly, in a nontrauma setting, especially oncology patients and patients with pyrexia of unknown origin, spinal reconstructions are routinely performed to assist in the detection of bone, paravertebral, and disc pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…4 This is primarily because they are more sensitive in detecting fractures compared with plain radiographs and avoid subjecting patients to a second CT spine study. 4 Similarly, in a nontrauma setting, especially oncology patients and patients with pyrexia of unknown origin, spinal reconstructions are routinely performed to assist in the detection of bone, paravertebral, and disc pathologies. 20 Image noise levels were significantly higher for reconstructed lumbar spine images from CTAP compared with L-spine CT, when both were reconstructed using SIR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with advanced DS affecting the facet joints, careful attention must be given to the posterior elements, as a fracture line extending there suggests an unstable injury (Fig 8). Therefore, the spine should be assessed by using spine CT protocols, not bone windows at CT of the neck, chest, abdomen, or pelvis (34). This is true for all rigid spine entities.…”
Section: Degenerative Spondylosismentioning
confidence: 99%
“… 5 Additional expense can be avoided by forgoing redundant CT studies; multiple studies have demonstrated the capabilities of reformatted images from abdominal or thoracic multidetector CT studies. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%